Liberal democracy, law and the citizen speaker : regulating online speech - Cram, Ian (London [England] : Hart Publishing, 2022)
"This book delivers an original, theoretically informed analysis of the legal regulation of online speech. Rejecting the narrow pluralism of elitist and deliberative accounts of the citizen's role in political discourse, the book defends a participatory account of speech in non-deliberative settings. The latter account of political pluralism best captures the republican democratic aspiration for popular, on-going authorship of the laws and the centrality of freedom to dissent in democratic theory. The legal and policy implications for governments and social media platforms of this inclusive envisioning of public discourse are then elaborated. In the digital world, anyone with access to the internet can be a speaker. Speech on public platforms has become democratized. At the same time, aspects of online speech are plainly problematic. Concerns exist about disinformation, 'fake news', 'deep fakes', 'weaponized speech' and 'trolls'. Offensive speech and the polarizing effects of robustly expressed political opinion are also troublesome. These assorted downsides of democratized speech are said to undermine the integrity of democratic processes and institutions. Public debate is distorted and coarsened and the electorate are misled. How ought the liberal democratic state respond to these challenges? The discussion is intended to be read by academics and researchers with interests in democratic theory, digital communications and freedom of expression. It offers a stimulating and distinctive contribution to debates about online speech."--
1. Damaging Democracy? -- 2. Legal norms, deliberative democracy and 'improved' public discourse -- 3. Rationality v Radical Pluralism -- 4. Official responses to problematic speech -- 5. Re-opening the channels of political change
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Internet -- Law and legislation; Freedom of speech; Freedom of information; Electronic books